2004
DOI: 10.1111/j.0956-7976.2004.00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Keeping It Short

Abstract: Research has shown that backward masking is a powerful tool for studying unconscious mental processes. Whereas studies have traditionally presented stimuli using cathode-ray tube (CRT) monitors or mechanical shutters together with slide projectors, recent studies (mainly in functional magnetic resonance imaging, fMRI) have begun to use methods based on liquid crystal displays (LCDs) and thin-film transistor (TFT) technology. However, because of differences in technology, all methods may not be equally suited f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 9 publications
(7 reference statements)
4
37
0
Order By: Relevance
“…A limitation of LCD projectors, which are easier to adapt to MR environments, is that they provide less precise control over the timing of visual presentation than traditional CRT displays. Nonetheless, recent studies have shown that LCD projectors still provide a high correspondence between desired and actual target durations, with trial-by-trial variability on the order of ϳ5 ms (Wiens et al 2004). Using a photodiode connected to an oscilloscope, we confirmed that our LCD projector was able to present changes in luminance up to the highest presentation rates used in the study (37.5 Hz).…”
Section: Experimental Design and Stimulisupporting
confidence: 76%
“…A limitation of LCD projectors, which are easier to adapt to MR environments, is that they provide less precise control over the timing of visual presentation than traditional CRT displays. Nonetheless, recent studies have shown that LCD projectors still provide a high correspondence between desired and actual target durations, with trial-by-trial variability on the order of ϳ5 ms (Wiens et al 2004). Using a photodiode connected to an oscilloscope, we confirmed that our LCD projector was able to present changes in luminance up to the highest presentation rates used in the study (37.5 Hz).…”
Section: Experimental Design and Stimulisupporting
confidence: 76%
“…7; see also Liang & Badano, 2007;Wiens et al, 2004), the present estimates highlight the substantial improvement in temporal response characteristics brought about by overdrive technology. For example, our estimated rise time of 1-6 ms is considerably shorter than estimates obtained without overdrive (2-25 ms in our estimates, 20-150 ms in past research; Liang & Badano, 2007;Wiens et al, 2004) and approaches that of CRTs (<1 ms). Clearly, recent advances in LCD technology have resulted in a substantial reduction in response times, making LCD screens suitable for presenting brief displays.…”
Section: General Discussion and Conclusionsupporting
confidence: 50%
“…Earlier estimates of the time to reach maximum luminance in LCD screens have ranged up to 47 ms for black-to-white transitions (Wiens et al, 2004) and up to 150 ms for gray-togray transitions (Liang & Badano, 2007). Those estimates, however, were obtained before the advent of overdrive technology, which boosts the voltage applied to the liquid crystals, thereby markedly improving the temporal response characteristics of LCD screens.…”
Section: Part Ii: Photometric Estimates Of Luminancementioning
confidence: 99%
“…The response time also differs depending on the target gray levels (Elze & Tanner, 2009;Liang & Badano, 2007). Wiens et al (2004) suggested that LCDs (earlier than 2004) were not suitable for psychological experiments requiring high temporal precision in stimulus presentations. They compared the temporal accuracy of an LCD with that of a raster scan CRT display by manipulating the duration of stimulus presentations from 8 to 200 msec and found that the LCD provided poor accuracy: Specifically, the LCD failed to present a target on some trials.…”
mentioning
confidence: 99%